Water vapor continuum in the range of rotational spectrum of H2O molecule: New experimental data and their comparative analysis. (January 2017) - Odintsova, T.A.; Tretyakov, M.Yu.; Pirali, O.; Roy, P.
Abstract: We present laboratory measurements of the water vapor continuum absorption in the far-IR region from 14 to 200 cm −1 . These data were obtained using a Fourier Transform spectrometer IFS125 HR associated with a multipass absorption cell and with the synchrotron far-IR broadband radiation extracted by the AILES beamline of SOLEIL facility. The spectra were recorded at room temperature (296 K) and pressures ranging from 2.73 to 15.1 mbar. A comparison with presently available experimental data is presented and the nature of the possible contributors to the continuum is discussed. The new data considerably extend and unify diverging results of previous measurements of the continuum performed in several spots within the range from about 3 cm −1 up to 84 cm −1 . The new evidence of significant contribution of the water dimer to the continuum formation is revealed in the range of 14–35 cm −1 . Analysis of the possible cause of the observed continuum indicates that its significant part in the range of the maximum intensity of water monomer rotational spectrum cannot be explained within the current understanding of the continuum origin. Highlights: Water vapor continuum spectra in the range 14–200 cm −1 are studied. Compromise of divergent previous measurements in the range 3–84 cm −1 is obtained. Dominant contribution of water dimer near 17 cm −1 is demonstrated. "Excess" continuum absorption is revealed and evaluated.